Relações entre Rigidez Arterial, Atividade Física e Idade Cronológica - Fernanda Sofia Amor Pereira (2018)
Primary ageing and cardiovascular risk factors aggregation lead to vascular ageing. Physical activity and sedentary time modulate arterial stiffness. This study aims to describe the relationship between arterial stiffness, daily physical activity and chronological age, in apparently healthy adults. Methods: this is a cross-sectional study based on 487 participants (68% female) aged 18 yearsold or above. Arterial stiffness was assessed as carotid-femoral pulse wave velocity (cfPWV) through applanation tonometry. Daily physical activity was objectively assessed, and classified as sedentary time, light and moderate to vigorous intensities, and steps per day. Participants were stratified according to the age and grouped by age decades. Correlations between arterial stiffnessand physical activity were performed. For group's comparisons the independent t-test was used. Considering the whole sample, cfPWV, was positively correlated with sedentary time (r= 0.142; p= 0.017), and negatively correlated with light physical activity (r= -0.084; p= 0.160), moderate-to-vigorous physical activity (r= -0.200; p= 0.01), and steps per day (r= -0.193; p= 0.01). For the agestage 60-69 years, cfPWV was significantly lower in participants that accomplished international physical activity guidelines (9.9 ± 2.06 m/s) compared to those that did not (10.64 ± 2.04 m/s; p= 0.043). Results suggest that arterial stiffness and physical activity and sedentary time are correlated along the ageing process. Additionally, the accomplishment with physical activity guidelines are characterized by a lower arterial stiffness, what might have important implications for cardiovascular risk management.